2022
DOI: 10.3390/pr11010072
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Major Extraction Variables to Improve Recovery of Anthocyanins from Elderberry by Response Surface Methodology

Abstract: Elderberry, which is well known for its richness in anthocyanin, is attracting attention in the bioindustry as a functional material with high antioxidant capacity. The aim of this study is to optimize extraction conditions to more effectively recover anthocyanins from elderberry. In a fundamental experiment to determine the suitable solvent, various GRAS reagents, such as acetone, ethanol, ethyl acetate, hexane, and isopropyl alcohol, were used, and total phenol and anthocyanin contents were detected as 9.0 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 75 publications
1
5
0
Order By: Relevance
“…From 100 vol% to 50 vol% ethanol concentration, the dieckol yield gradually increased as more water was added to ethanol. This finding supports the notion that the extraction capacity of the ethanol solvent was enhanced by the addition of water, in line with earlier reports (Kim et al, 2022b;Brahmi et al, 2022). According to this preliminary study, ethanol concentration significantly affects the dieckol yield from EC, prompting us to designate "ethanol concentration" as one of the variables in the optimization study (Table 1).…”
Section: A Preliminary Study For Experimental Designsupporting
confidence: 91%
See 2 more Smart Citations
“…From 100 vol% to 50 vol% ethanol concentration, the dieckol yield gradually increased as more water was added to ethanol. This finding supports the notion that the extraction capacity of the ethanol solvent was enhanced by the addition of water, in line with earlier reports (Kim et al, 2022b;Brahmi et al, 2022). According to this preliminary study, ethanol concentration significantly affects the dieckol yield from EC, prompting us to designate "ethanol concentration" as one of the variables in the optimization study (Table 1).…”
Section: A Preliminary Study For Experimental Designsupporting
confidence: 91%
“…The dieckol yield in the ethanol extraction process can be improved by (1) preparing ethanol-based solvents with enhanced extraction capacity for dieckol, and (2) optimizing process variables. Aqueous organic solvents are generally used as efficient solvents for recovering polar phenolic compounds (Kim et al, 2022b). According to previous reports, binary solvents are more efficient in recovering phenolic compounds than mono-solvent, and water-solvent mixtures create a more polar medium, which can improve the extraction of phenolic compounds (Chaves et al, 2020;Sonar and Rathod, 2020).…”
Section: Extraction Capacity Of the Selected Gras Solvents For Diecko...mentioning
confidence: 99%
See 1 more Smart Citation
“…The total flavonoid content of PSEs was measured using a modified aluminum chloride colorimetric method [43]. Briefly, 50 µL of a sample and 30 µL of 5% NaNO 2 were mixed in an e-tube using a vortex mixer for approximately 10 s and then reacted for 6 min at 25 • C in a water bath.…”
Section: Determination Of Total Flavonoid Contentmentioning
confidence: 99%
“…PSO is a population-based meta-heuristic optimization algorithm motivated by the cooperative behavior of foraging animals such as flocks of birds or schools of fish. , Multiple linear regression (MLR) is a statistical analysis method used in machine learning. Few studies are using these methods for juice optimization. The combination of RSM, MLR, and PSO can provide more accurate results in component optimization in vegetable juices. When the literature was scanned, no studies were found investigating the optimization of parsley juice’s chlorophyll and ascorbic acid components with RSM, MLR, and PSO after ultrasound application.…”
Section: Introductionmentioning
confidence: 99%